2022
DOI: 10.1111/pedi.13405
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 diabetes incidence increased during the COVID ‐19 pandemic years 2020–2021 in Czechia: Results from a large population‐based pediatric register

Abstract: Background To explore type 1 diabetes incidence patterns during the pandemic years 2020 and 2021 in Czechia, to compare them to the trends from the previous decade, and to test its association with indicators of containment measures and of pandemic severity (school closing and the all‐cause excess mortality). Methods The Czech Childhood Diabetes Register is a population‐based incidence register recording patients age 0–14.99 years at diabetes onset. Type 1 diabetes inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…After the abstract review, we retrieved 81 full-text articles to determine eligibility. Forty-two records met the full inclusion criteria . The manual search of the included studies’ reference lists did not yield additional studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After the abstract review, we retrieved 81 full-text articles to determine eligibility. Forty-two records met the full inclusion criteria . The manual search of the included studies’ reference lists did not yield additional studies.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-four studies (57.1%) reported DKA incidence at diagnosis . Incident cases of type 1 and type 2 diabetes were reported in 36 studies (85.7%) and 9 studies (21.4%), respectively. Two studies (4.8%) did not distinguish between diabetes types .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, recent evidence suggests that COVID-19 may affect various organs in the body even after 30 days, the acute phase of infection, increasing the risk of non-communicable diseases in the extrapulmonary organs [5]. Several studies have shown that autoimmunity against pancreatic beta cells increased after COV-ID-19 which may also increase the risk of type 1 diabetes [6,7]. Additionally, small-scale studies have suggested that COV-ID-19 might increase the incidence of type 2 diabetes mellitus (T2DM) [8,9], and recent large cohort studies from national healthcare databases have also shown a risk of developing diabetes [10][11][12].…”
Section: Introductionmentioning
confidence: 99%